О некоторых приёмах работы над ритмикой и интонацией в преподавании РКИ - ТЮРИНА, ЮЛИАНА ЮРЬЕВНА (SlavVaria, 2021)
About some techniques of working on rhythm and intonation in teaching Russian as a foreign language (RFL). Accent-centricity of the Russian phonetic word is an important aspect of the study of RFL and the correct pronunciation. Verbal stress is not only the basis of the rhythmic organization of a phonetic word, but also an integral part of the intonation of the utterance. The article contains practical recommendations that simplify and speed up the process of mastering rhythmic patterns and intonation structures of the Russian language.